Who Knew Hemorrhoids Could Be Profound? A Reflection on LGBTQ Health care at the US-Mexican Border - Hill, Elena (Ars Medica, 2022)
This is a narrative medicine piece that reflects on my interaction with an LGBTQ patient seeking asylum at the US-Mexican border during my time volunteering as a family physician with an NGO there. The piece tells her narrative and outlines her struggle to get health care. It ultimately calls for the re-examination of services available to this vulnerable population in the midst of our country’s ongoing immigration crisis. It highlights the role that family physicians like myself can have in providing care to this community.